Particle precipitations during NEIAL events : simultaneous ground based observations at Svalbard - Lunde, June; Lorentzen, Dag Arne; Ogawa, Y; Gustavsson, B; Ogawa, Yasunobu; Løvhaug, U.P. (Copernicus, 2007)
In this paper we present Naturally Enhanced Ion Acoustic Lines (NEIALs) observed with the EISCAT Svalbard Radar (ESR). For the first time, long sequences of NEIALs are recorded, with more than 50 events within an hour, ranging from 6.4 to 140 s in duration. The events took place from ~08:45 to 10:00 UT, 22 January 2004. We combine ESR data with observations of optical aurora by a meridian scanning photometer at wavelengths 557.7, 630.0, 427.8, and 844.6 nm, as well as records from a magnetometer and an imaging riometer. The large numbers of observed NEIALs together with these additional observations, enable us to characterise the particle precipitation during the NEIAL events. We find that the intensities in all optical lines studied must be above a certain level for the NEIALs to appear. We also find that the soft particle precipitation is associated with the down-shifted shoulder in the incoherent scatter spectrum, and that harder precipitation may play a role in the enhancement of the up-shifted shoulder. The minimum energy flux during NEIAL events found in this study was ~3.5 mW/m2 and minimum characteristic energy around 50 eV.